A Novel Function of Extraerythrocytic Hemoglobin - Yoshida, Etsuo; Ohmura, Sayuri; Sugiki, Masahiko; Anai, Keita; Maruyama, Masugi (Thrombosis and Haemostasis, 2001)
Following wounding, the surrounding fibroblasts migrate towards the clotted blood in the wounded space to form granulation tissue resulting in wound repair. One of the most abundant proteins in the wound is hemoglobin (Hb). The aim of the present study was to examine the effect of Hb on fibroblasts in producing components of the plasminogen-plasmin system which play an important role in wound healing. Human Hb Ao added to cultures of human fibroblasts elicited a dose-dependent increase in fibrinolytic activity. ELISA demonstrated an increased fibrinolytic activity due to increased urokinase-type plasminogen activator (uPA). An increase in tissue-type PA was also detected, while the type-1 PA inhibitor level remained unaffected. Globin showed a similar effect, while hemin and protoporphyrin IX exerted no effect. The influence of Hb was quenched when haptoglobin was added. Although northern blot analysis revealed no difference in uPA transcripts between stimulated and non-stimulated cells, immunopretipitation experiments confirmed an increased uPA synthesis in Hb- and globin-treated cells, suggesting that enhanced expression is achieved through translational regulation. These findings suggest a potential role for globin in modulating cellular functions during the process of wound healing.
Keywords: Hemoglobin; globin; wound healing; the plasminogen-plasmin system; fibrinolytic system; plasminogen activator